Pranksters vs. Autocrats Why Dilemma Actions Advance Nonviolent Activism - Popovic, Srdja (Brown Democracy Medal, 2022)
The Lawrence and Lynne Brown Democracy Medal, presented by the McCourtney Institute for Democracy at Penn State, recognizes outstanding individuals, groups, and organizations that produce innovations to further democracy in the United States or around the world. The 2020 Brown Democracy Medal winner, Srdja Popovic, was a leader in the revolution that brought down the Milošević regime in Serbia and he continues to help protestors around the world learn effective, sometimes humorous, nonviolent tactics. In 2020, he teamed up with Sophia A. McClennen to study the concept of "dilemma actions," which offers a structured, strategic approach to fighting back against authoritarianism, as well as for defending democracy.